Basic Principles (Indicators) for Assessing the Technical and Economic Potential of Developing Arctic Offshore Oil and Gas Fields - Gennady Stroykov; Yurii N. Vasilev; Oleg V. Zhukov (Journal of Marine Science and Engineering, 2021)
Sustainable development of the Arctic is the main priority of the state policy regarding regional development of the Russian Federation. The study of the Arctic zone of the Russian Federation for the formation of principles, methods and strategies, as well as organizational and economic mechanisms for its sustainable development is topical at present. This article deals with one of the strategic decision-making tools used in the process of implementing the development program for the Russian Arctic, namely, the assessment of the technical and economic potential of the Arctic fields. The purpose of this assessment is to rank the fields according to the priority of their commissioning for a more optimal distribution of costs in the development of Arctic resources. This paper presents the results and methodology of technical and economic potential estimation in general, and the potential of the Arctic oil and gas fields in particular. An analysis of the conceptual apparatus in the field of the evaluation of various types of potential is carried out. The methodology for assessing the technical and economic potential of a field are investigated. The problems arising in the process of such an assessment are revealed. Recommendations for improving the methodology of assessing the technical and economic potential of oil and gas fields in the Arctic are given. The necessity of expanding the list of indicators for assessing the technical and economic potential of these fields, taking into account current trends, has been noted. A list of 10 technical and 26 economic indicators to assess the technical and economic potential of the development of offshore Arctic fields is proposed.